HSP27 Protects Skin From Ultraviolet B -Induced Photodamage by Regulating Autophagy and Reactive Oxygen Species Production - Wang, Zi-Yue; Li, Ang; Huang, Xin; Bai, Gen-Long; Jiang, Yu-Xin; Li, Ruo-Lin; Liu, Chuan; Wen, Zhu-Yuan; Wang, Ping; Chen, Ai-Jun (Frontiers in Cell and Developmental Biology, 2022)
Ultraviolet (UV) irradiation has been well documented to be linked with almost all skin problems we can think of, both the dermis and the epidermis may be affected to varying degrees. Every time when exposed to sunlight without protection, our skin steps closer to photoaging, leading to irreversible consequences ultimately. Heat Shock Protein 27 (HSP27) is a vital protein involved in cell growth, autophagy, apoptosis, drug resistance, tumor genesis and metastasis. Evidence suggests that the organism was subjected to various internal and external environmental stress (heat, oxidative stress, organic toxicants and so on), HSP27 has protective function with high expression. Whereas, the impressions of HSP27 coped with UV irradiation have not been examined thoroughly. In this study, photodamage models were developed through different doses of UVB irradiation in human epidermal keratinocytes (HEKs) (30 mj/cm²), human dermal fibroblasts (HDFs) (150 mj/cm²) and mouse skin (2700 mj/cm²). HSP27 knockdown decreased cell viability and increased the incidence of UVB-induced ROS production. We’ve got consistent results in vivo and vitro. The expression of LC3 B was significantly lower in the UVB+si-HSP27 group compared with the UVB group, while P62 was significantly higher. It was also revealed that HSP27 knockdown reduced some antioxidants expression, such as superoxide dismutase (SOD), catalase (CAT), which accelerated UVB-induced ROS release. Moreover, histological results showed that epidermis was thickened and collagen fibers were disorganized in the UVB+si-HSP27 group. These findings has demonstrated that HSP27 might play a photoprotective role in the UVB-induced skin damage process by maintaining the normal autophagy and antioxidant level. It implies that HSP27 could be a potential therapeutic target of photodamage. However, determination of the definitive mechanism requires further exploration.